Discovery and development of a novel class of phenoxyacetyl amides as highly potent TRPM8 agonists for use as cooling agents. Issue 16 (15th August 2017) - Noncovich, Alain; Priest, Chad; Ung, Jane; Patron, Andrew P.; Servant, Guy; Brust, Paul; Servant, Nicole; Faber, Nathan; Liu, Hanghui; Gonsalves, Nicole S.; Ditschun, Tanya L.
Graphical abstract: Abstract: The paper presents the activity trends for a novel series of phenoxyacetyl amides as human TRPM8 receptor agonists. This series encompasses in vitro activity values ranging from the micromolar to the picomolar levels. Sensory evaluation of these molecules highlights their relevance as cooling agents for oral applications. The positive outcome of the complete evaluation of N -(1 H -pyrazol-3-yl)- N -(thiophen-2-ylmethyl)-2-( p -tolyloxy)acetamide resulted in its approval for Generally Recognized As Safe (GRAS) status by the Flavor & Extract Manufacturer Association (FEMA) as FEMA 4809.